2013
DOI: 10.1128/aac.00499-13
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole Assists Berberine To Kill Fluconazole-Resistant Candida albicans

Abstract: It was found in our previous study that berberine (BBR) and fluconazole (FLC) used concomitantly exhibited a synergism against FLC-resistant Candida albicans in vitro. The aim of the present study was to clarify how BBR and FLC worked synergistically and the underlying mechanism. Antifungal time-kill curves indicated that the synergistic effect of the two drugs was BBR dose dependent rather than FLC dose dependent. In addition, we found that BBR accumulated in C. albicans cells, especially in the nucleus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 50 publications
1
61
0
Order By: Relevance
“…A recent study has demonstrated that berebrine can assist fluconazole to kill fluconazole-resistant C. albicans (32). The present results further indicate the possible sensitization of various pathogenic fungi to other standard drugs by berberine and berberrubine, with the purpose of obtaining an increment in the antifungal potency.…”
Section: Determination Of Mic Mfc and Sensitization Assaysupporting
confidence: 50%
“…A recent study has demonstrated that berebrine can assist fluconazole to kill fluconazole-resistant C. albicans (32). The present results further indicate the possible sensitization of various pathogenic fungi to other standard drugs by berberine and berberrubine, with the purpose of obtaining an increment in the antifungal potency.…”
Section: Determination Of Mic Mfc and Sensitization Assaysupporting
confidence: 50%
“…Collectively, based on the present results, it may be speculated that IMP had synergistic effects with BEB via increasing the accumulation of BEB in the intracellular space of P. aeruginosa cells. However, whether the ingressive BEB finally caused cell cycle arrest and DNA damage similar to its effects in Candida albicans still requires to be elucidated (13).…”
Section: Discussionmentioning
confidence: 99%
“…Due to this IMP resistance in P. aeruginosa novel antibacterial agents are urgently required. Berberine (BEB), a natural isoquinoline alkaloid, is prevalent in numerous medicinal plants and has been demonstrated to have antibacterial and antifungal activities alone or in combination with other drugs (9)(10)(11)(12)(13). In a previous study, BEB was reported to be a potential inhibitor of MexXY-mediated resistance in P. aeruginosa (14).…”
Section: Introductionmentioning
confidence: 99%
“…FCZ is undergoing clinical testing and has been shown to have minimal toxicity (3,34). Many strains of C. albicans are resistant to FCZ therapy, while FCZ can be cytotoxic at high concentrations (15,35).…”
Section: Discussionmentioning
confidence: 99%
“…This yeast normally lives on the skin and mucous membranes without causing infection. However, overgrowth of these microbes can cause superficial mycoses, invasive mucosal infections, and disseminated systemic disease, particularly in AIDS patients, transplant recipients, and other immunocompromised people (2,3). It is well documented that the emergence of drug-resistant C. albicans is increasing at an alarming pace (4)(5)(6).…”
mentioning
confidence: 99%